Legal Regulation of Smart Contracts - Nodirakhon ABDURAKHMANOVA (Periodica Journal, 2023)
In the rapidly evolving landscape of technology and finance, smart contracts have emerged as a groundbreaking innovation that holds the potential to revolutionize how agreements are executed and enforced. Smart contracts are self-executing contracts with the terms of the agreement directly written into code. While they offer numerous advantages, their integration into traditional legal frameworks presents challenges that require careful consideration. This article delves into the legal regulation of smart contracts, exploring their benefits, challenges, and the current state of legal recognition
Keywords: contract; computer protocol; cryptocurrency